2022
DOI: 10.52114/apjhad.1126565
|View full text |Cite
|
Sign up to set email alerts
|

The Seismic Performance of Reinforced Sustainable Concrete Low-Rise Structures

Abstract: The utilization of sustainable concrete in producing reinforced concrete structures subjected to seismic actions is one of the leading research topics of recent years. With the technical exhibition that this concrete may be used in conventional reinforced concrete structures, a significant threshold for this sustainable material is accomplished. In the scope of this study, the seismic behavior of five different reinforced concrete structures under seismic actions, which are considered to be produced from susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…[12] investigated experimentally the impact of steel bers on the shear behavior of concrete deep beams using 100% recycled concrete aggregate (RCA). SARIBAŞ [13] used RCA in four different ratios: 25%, 50%, 75%, and 100%. It was found that deep beams with 25% and 50% RCA behaved similarly to conventional deep beams.…”
Section: Introductionmentioning
confidence: 99%
“…[12] investigated experimentally the impact of steel bers on the shear behavior of concrete deep beams using 100% recycled concrete aggregate (RCA). SARIBAŞ [13] used RCA in four different ratios: 25%, 50%, 75%, and 100%. It was found that deep beams with 25% and 50% RCA behaved similarly to conventional deep beams.…”
Section: Introductionmentioning
confidence: 99%